2019
DOI: 10.1038/s41467-019-13819-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast valence to non-valence excited state dynamics in a common anionic chromophore

Abstract: Non-valence states in neutral molecules (Rydberg states) have well-established roles and importance in photochemistry, however, considerably less is known about the role of non-valence states in photo-induced processes in anions. Here, femtosecond time-resolved photoelectron imaging is used to show that photoexcitation of the S1(ππ*) state of the methyl ester of deprotonated para-coumaric acid – a model chromophore for photoactive yellow protein (PYP) – leads to a bifurcation of the excited state wavepacket. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 73 publications
8
79
0
Order By: Relevance
“…Additionally, Zewail and coworkers observed an oscillation in the high kinetic energy window, similar to that observed in ε 1 , but not the out-of-phase oscillation at lower energy (ε 2 ), probably because of contamination by autodetachment 16 . Dynamics involving isomerisation were also observed in a recent study on a closely related PYP chromophore anion in which the ketone is replaced by an ester group 31 . These dynamics were in competition with internal conversion to a non-valence state of the anion.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, Zewail and coworkers observed an oscillation in the high kinetic energy window, similar to that observed in ε 1 , but not the out-of-phase oscillation at lower energy (ε 2 ), probably because of contamination by autodetachment 16 . Dynamics involving isomerisation were also observed in a recent study on a closely related PYP chromophore anion in which the ketone is replaced by an ester group 31 . These dynamics were in competition with internal conversion to a non-valence state of the anion.…”
Section: Discussionmentioning
confidence: 54%
“…54 and references therein). Interconnections between valence states of anions and dipole-bound states have also been identified in the opposite direction (bifurcation of the excited state wavepacket leading to the formation of a non-valence state) for a common anionic chromophore, 55 and the stability of such orbitals in the presence of perturbing molecules has also been studied by the same group. 56 Very recently, Anstöter et al 57 showed that the observed emission peaks from the vibrational structure of the nitrobenzene anion can be correlated with an autodetachment mechanism via dipole-bound state formation.…”
Section: And References Therein)mentioning
confidence: 99%
“…Although the initial geometry of the resonance M −Ã is different than in electron attachment, the same two types of excitation or emission are usually considered. A structured PE signal with low and constant ε f has also been seen over a range of hv in a number of targets, and this structure has been related to autodetachment from nonvalence states [10][11][12]. Here, we probe the electron detachment from electronic resonances in nitrobenzene (NB) using both 2D EEL and 2D PE spectroscopy in an attempt to gain insight into this structured low-energy electron emission channel.…”
mentioning
confidence: 99%
“…There are two mechanisms by which the DBS can be populated. The first is by internal conversion through a conical intersection from a valence resonance [10][11][12]. For the second, a fraction of the population of the resonance internally converts to reform the vibrationally hot ground state of the anion, which could then populate the DBS.…”
mentioning
confidence: 99%
See 1 more Smart Citation